Post-natal cardiomyocytes can generate iPS cells with an enhanced capacity toward cardiomyogenic re-differentation - Rizzi, R (Nature Publishing Group, 2012)
Adult mammalian cells can be reprogrammed to a pluripotent state by forcing the expression of a few embryonic transcription factors. The resulting induced pluripotent stem (iPS) cells can differentiate into cells of all three germ layers. It is well known that post-natal cardiomyocytes (CMs) lack the capacity to proliferate. Here, we report that neonatal CMs can be reprogrammed to generate iPS cells that express embryonic-specific markers and feature gene-expression profiles similar to those of mouse embryonic stem (mES) cell and cardiac fibroblast (CF)-derived iPS cell populations. CM-derived iPS cells are able to generate chimeric mice and, moreover, re-differentiate toward CMs more efficiently then either CF-derived iPS cells or mES cells. The increased differentiation capacity is possibly related to CM-derived iPS cells retaining an epigenetic memory of the phenotype of their founder cell. CM-derived iPS cells may thus lead to new information on differentiation processes underlying cardiac differentiation and proliferation.